Preliminary reverse impulse in SC (Y) at off - equatorial stations in India - Rastogi, R.G.; Ahmed, K. (My University, 2010)
The storm sudden commencement (SSC) at 2345 hrs UT on 24 September 1998, occurring at around local sunrise for Indian stations had produced uniquely two–step impulses on the H magnetogram at all stations. The amplitude ∆H had increased progressively from Trivandrum to Gulmarg, unlike the characteristic of the day time equatorial enhancement of SC (H). The solar wind parameters too showed abnormal variations during the period of SC. The magnetogram trace for declination (or eastward field Y) recorded a preliminary reverse impulse (PRI) close to the latitude of Sq focus at stations Gulmarg, Ujjain, Nagpur and Shillong. The PRI was absent in SC (Y) at equatorial stations Trivandrum and Pondicherry. This observations show a new complex relationship between the ionospheric dynamo and magnetospheric dawn / dusk electric field with the equatorial geomagnetic field around sunrise.
Keywords: Preliminary reverse impulse (PRI); Sudden storm commencement (SSC); Geomagnetic eastward component